2009
DOI: 10.1002/ejoc.200900014
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Promoted Synthesis of N‐Heterocycles by Tandem Imination/Annulation of γ‐ and δ‐Ketoalkynes in the Presence of Ammonia

Abstract: The synthesis of 3‐substituted 1‐methylpyrrolo[1,2‐a]pyrazines and 3‐substituted isoquinolines was achieved by the intramolecular cyclisation of 2‐acetyl‐1‐propargylpyrroles and 2‐alkynylbenzaldehydes, respectively, in the presence of ammonia under microwave heating. The tandem imination/annulation of 2‐alkynylbenzaldehydes was easily accomplished under standard conditions, while TiCl4 was used to achieve pyrrolo[1,2‐a]pyrazines. The reaction mechanism and the regioselectivity were discussed on the basis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 78 publications
2
41
0
Order By: Relevance
“…A more comprehensive study showed that microwaves heating gave comparable or better yields in reduced reaction times (Scheme 8) [17]. The product derived from a 5-exo-dig cyclization mode has never isolated or Isoquinoline heterocycles have been also prepared in excellent yields via copper-catalyzed cyclization of tert-butylimine derivatives of 2-alkynylbenzaldehydes [18].…”
Section: Resultsmentioning
confidence: 98%
“…A more comprehensive study showed that microwaves heating gave comparable or better yields in reduced reaction times (Scheme 8) [17]. The product derived from a 5-exo-dig cyclization mode has never isolated or Isoquinoline heterocycles have been also prepared in excellent yields via copper-catalyzed cyclization of tert-butylimine derivatives of 2-alkynylbenzaldehydes [18].…”
Section: Resultsmentioning
confidence: 98%
“…The reaction proceeded by a cyclocondensation of diaminomalonitrile with ketones (e.g., acenaphthenequinone, 245) or an ester 246 in the presence of triethylamine in ethanol (Scheme 52), and the expected products were obtained with good to excellent yields. Moreover, Alfonsi et al [233] have reported the synthesis of pyrazines derivatives and other series of N-heterocycles 250, 251 by tandem imination/annulation of γ-and δ-ketoalkynes 249. The reaction was achieved by the intramolecular cyclization of 2-acetyl-1-propargylpyrroles in the presence of ammonia Original synthetic heterocycles, such as substituted dicyanopyrazines 247, 248, have been synthesized using a domestic MW oven [232].…”
Section: Scheme 48 Mw-assisted Ugi 4-component Reaction Leading To Pmentioning
confidence: 99%
“…Mechanistic study of the isoquinolines synthesis reported by Alfonsi et al [233] Scheme 56. Mechanistic study of the isoquinolines synthesis reported by Alfonsi et al [233] Derivatives of 2(1H)-pyrazinones are considered as important scaffolds for drug design due to their widespread biological activities [234][235][236][237][238][239]. In this context, Gising et al [237] have reported a rapid and versatile one-pot MW-assisted two steps synthesis of N-1 and C-6 functionalized 3,5-dichloro-2(1H)-pyrazinones 258.…”
Section: Scheme 48 Mw-assisted Ugi 4-component Reaction Leading To Pmentioning
confidence: 99%
“…Using para-substituted styrene oxides (Cl, F) the regio-and diastereoselectivity of the reaction were proven, and also for the nucleophilic ring opening of epoxides derived from para-substituted β-methylstyrene oxides [58]. Xue were accessible from the respective 2-alkynylbenzaldehydes with yields ranging from 21 to 89% (Scheme 11.20) [60]. In contrast to reactions of alkynylpyrroles, the 5-exo-dig-cylization, which would lead to 1-alkylidene-1H-isoindoles, is forbidden.…”
Section: Reactions With Ammonia and Hydrogen Sulfidementioning
confidence: 99%
“…alkynylpyrroles with NH 3 dissolved in MeOH (Scheme 11.20)[60]. Stereoselective 6-exo-dig-cyclization of the imine intermediate afforded 3,4-dihydropyrrolo[1, 2-a]pyrazines, which undergo double-bond isomerization under basic conditions to pyrrolo[1,2-a]pyrazines.…”
mentioning
confidence: 99%